Beyond the Curriculum: Exploring the Influence of Islamic Values and Teacher Role Models on Student Character Formation - Abdul Wahid Zaini (AFKARINA: Jurnal Pendidikan Agama Islam, 2024)
This research explores the integration of Islamic values in character education and the critical role of teachers as role models within the framework of contextual learning. The primary objective of this study is to examine how the application of contextual teaching methods, combined with the consistency of teacher behavior, influences the internalization of character values among students at Nurul Jadid Junior High School, Kraksaan. A qualitative approach was employed using a case study method, allowing for an in-depth exploration of teachers' experiences and the dynamics within the classroom. Data were collected through in-depth interviews, participatory observations, and document analysis, and subsequently analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing/verification. The findings reveal that integrating character values such as honesty, responsibility, tolerance, and cooperation into the curriculum, supported by teachers acting as role models, significantly enhances the character development of students. The implications of this research underscore the importance of developing contextual teaching strategies and ensuring consistent teacher behavior to foster effective character education. This study contributes significantly to the literature on character education, particularly within the context of Islamic Religious Education.